Strategi Pembelajaran Pendidikan Agama Islam Berbasis Blended Learning - Firsya Yunia Amanda; Nurul Ashiqin; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2024)
The development of digital technology has brought significant changes to the world of education, including Islamic Religious Education (PAI) learning. These changes are caused by the potential and capabilities of information and communication technology which enable humans to have relationships and fulfill their needs for unlimited information. This article reviews Islamic religious education strategies based on blended learning. Blended learning is an educational method that combines face-to-face learning with online learning. In this article, we will explain how Islamic religious education strategies can be implemented using blended learning. By combining various learning methods and resources, this approach aims to increase the effectiveness of Islamic learning.